AKIBAT HUKUM WANPRESTASI TERHADAPAKTA KESEPAKATAN BERSAMA YANG DIBUAT DI HADAPAN NOTARIS (STUDI KASUS PUTUSAN PENGADILAN NEGERI BEKASI NOMOR 339/PDT.G/2019/PN.BKS) - Herman Joseph; Ariawan Gunadi (Jurnal Hukum Adigama, 2022)
The application of the law is an application that has been determined by the government as areflection of the rules that must be obeyed by law enforcement of icials and the public. Agreement is anegotiated and typically legally binding arrangement between parties as to a course of action theabsence of incompatibility between two things. In agreement, there are the terms called default (breachof contract). Default refers to non-fulfillment of an 'achievement' in the agreement which can be afailure to, do something, not do something, or pay an amount. Breach refers to breaches of anagreement in general, such as violations of the statements and guarantees, not cheating and so on,including default. It can be said that if a party is in default, that party is definitely in breach (ofcontract), but if a party is in breach (of contract), that party is not necessarily declared a default withall the consequences Based on article 1243 of the Civil Code which states that the definition of defaultis "reimbursement of costs, losses and interest due to non-fulfillment of an engagement, then itbecomes mandatory, if the debtor, after being declared negligent in fulfilling his engagement, continuesto neglect it, or if something must be given or made, can only be given or made, can only be given ormade within the deadline that has been passed”